Teacherâs Role in Managing the Class during Teaching and Learning Process - Rindu, Ignatius; Ariyanti, Ariyanti (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
The purpose of this research is to investigate teacherâs roles which used by the English teacher in managing the class during the teaching and learning process at SMP Advent Samarinda. The research methodology used is descriptive design with qualitative approach which is aimed to describe the real situation in the field. In collecting the data, the researcher used questionnaires, observation sheet, field note and interview guide as the instruments. Moreover, the research subject is an English teacher who teaches at seventh and eighth grades of SMP Advent Samarinda. The result of the research is the teacher runs nine roles in they are as a controller, an assessor, an organizer/manager, a prompter/motivator, participant, a resource/informer, a facilitator, a demonstrator, and as a guide. There are roles which are preeminent which most applied by the teacher such as teacher as a controller and teacher as an assessor. It is shown by the result of studentsâ respond in the questionnaire, restrictive questions; 77% and 68% and free answer; 68% and 100%, which also found in the time the researcher did the observation. On the contrary, the teacherâs roles as a prompter and as a resource have not been played maximally by the teacher.